A contar amabilidad : diez formas de darles la bienvenida a ninos refugiados = Counting kindness : ten ways to welcome refugee children - Kurman, Hollis; Barroux; Calvo, Carlos E.; Kurman, Hollis; Kurman, Hollis (Watertown, MA : Charlesbridge, 2021)
Follow the journey of immigrant and refugee children from leaky boat to a new country, a new school, and new friends in this simple counting book.
Originally published in English in 2020 under title: Counting kindness.
Includes bibliographical references.
Text in Spanish and English.
Keywords: Immigrant children -- Juvenile fiction; Refugee children -- Juvenile fiction; Kindness -- Juvenile fiction; Counting -- Juvenile fiction; Immigrants -- Fiction; Refugees -- Fiction; Kindness -- Fiction; Counting; Spanish language materials -- Bilingual